Implementation of Tax Planning at PT Mayora Indah - Nur Israq Fauziah; Ida Farida; Memen Kustiawan (Jurnal Riset Perpajakan: Amnesty, 2024)
This research investigates the implementation of tax planning at PT. Mayora Indah, a prominent food production company in Indonesia. The study employs a descriptive data analysis method to assess tax planning using the fixed asset depreciation method, focusing on financial reports from 2021 to 2022. The primary objective is to analyze the impact of different depreciation methods on income tax payments. In the introduction, the significance of tax planning is highlighted as a crucial aspect of organizational management, emphasizing the need to comply with tax regulations while minimizing tax liabilities. The study specifically delves into the tax planning strategy related to fixed asset depreciation methods, examining their implications on tax obligations. The literature review covers essential concepts such as tax planning, influencing factors in taxpayer behavior, and various tax planning strategies, including tax saving, tax avoidance, and optimizing allowable tax credits. It also discusses the classification and depreciation of fixed assets in taxation, outlining different groups and depreciation rates. The research methodology is comparative, employing descriptive methods to analyze the implementation of tax planning at PT. Mayora Indah. The results of the analysis indicate that the straight-line depreciation method results in higher taxes compared to the declining balance method for the years 2021 and 2022. The company profile provides an overview of PT. Mayora Indah, emphasizing its market presence, vision, and mission. The analysis of the results of tax implementation using the depreciation method includes income calculations, depreciation expenses, taxable business profits, and income tax calculations for both straight-line and declining balance methods. The conclusion highlights that the declining balance method yields smaller taxes compared to the straight-line method, demonstrating the effectiveness of tax planning through fixed asset depreciation. The study suggests that PT. Mayora Indah can achieve significant cost savings by implementing the declining balance method in its tax planning strategy.